Two root canals in maxillary central incisor - Fábio de Almeida-Gomes; Nadine Luísa Soares de Lima Guimarães; Claudio Maniglia-Ferreira; Roberto Alves dos Santos; Marcelo de Morais Vitoriano; Bruno Carvalho de Sousa (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: The success of endodontic treatment requires the knowledge of tooth morphology and its variations. Case report: This clinical article reports an unusual root canal configuration that was detected in a maxillary central incisor with two root canals, demonstrated by radiographic and computerized tomography exams. Conclusion: Knowledge of endodontic anatomy as well as the obtainment of both preoperative radiographs and tomography is important to detect abnormal tooth morphology.